Social perceptions of the value of green spaces: A view from the South - Cilliers, Elizelle Juanee (Frontiers in Sustainable Cities, 2023)
Despite the expanding scientific understanding that green spaces are substantially beneficial to urban communities and their host cities, along with the evidence that some global cities are making progress to include nature as part of mainstream planning, this paper argues that social perceptions also play a critical part in the successful planning and realization of urban green space provision in practice, especially in the Global South. This research thus reflected on the pedagogical effect on social perception about the presence of green spaces in urban area. To understand the impact of social perceptions on the valuation of green spaces, this paper investigated the views of a convenience sample of professionals working in the Built Environment in South Africa, and employed frequency distribution, two-way frequencies, and statistical measures to draw conclusions pertaining to perception of green space value. The research illustrated that social perceptions inform how urban risks are perceived and that these perceptions of green space are often limited due to a lack of knowledge and awareness. The research exemplified that the actual community benefit provided by green spaces should be better articulated to gain traction in practice, and that the appreciation and use of these urban green spaces should also be understood from a context-based and personal valuation perspective, in order to position these spaces as the critical resource and public good. This research concluded that social perceptions should be comprehensively understood, especially in quest of realizing green(er) spaces and cities in the Global South.